ChemInform Abstract: Impact of Carbon Insertion on the Microstructure and Magnetic Properties of Nanocrystalline Pr2Co7 Alloys. Issue 41 (19th September 2013) - Fersi, R.; Cabie, M.; Mliki, N.; Bessais, L.
Abstract Pr2Co7Cx carbides (x = 0, 0.25, 0.5, 0.75) are prepared by arc melting of pure components in stoichiometric proportions followed by high energy ball milling and annealing at 873—1323 K.